Spliced adenovirus-associated virus RNA. - Laughlin, C A (Proc Natl Acad Sci U S A, 1979)
We describe the structure of cytoplasmic RNA species transcribed from the DNA of adenovirus-associated virus, a defective parvovirus. The RNA was hybridized with minus strand template DNA and visualized in the electron microscope. Alternatively, the DNA.RNA duplex molecules were digested with nuclease S1 or Escherichia coli exonuclease VII and analyzed by agarose gel electrophoresis. A set of RNA species was observed with 5' terminal at map positions 5, 13, 19, or 39 and a 3' terminus and poly(A) tail at position 96 (one map unit is equivalent to 1% of genome length). Most of these RNAs are spliced and lack sequences approximately between positions 40 and 49. Some RNA preparations also contained unspliced molecules with 5' and 3' terminal at positions similar to those in the spliced RNA. IMAGES: